Identificacion molecular de Oxysporum latemarginatus (Basidiomycotina) en palmeras - Martin, M.P.=700 1 Monton, C.
(Es, En)
ilus., 7 ref.
Keywords: PHOENIX CANARIENSIS; PODREDUMBRES; BASIDIOMYCOTINA; HONGOS; ESPAÑA